Survey on Senior High School Basket Ball Extracurricular During Pandemic in Bangkalan District - Elma Safitri; Fajar Hidayatullah; Khoirul Anwar (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2021)
The study was conducted because it wanted to provide information about student activities in basketball extracurricular activities for junior high school students in Bangkalan Regency during the COVID19 pandemic. This study uses a quantitative research approach using survey methods with questionnaires or questionnaires. This study aims to 5 schools that have been surveyed with 91 students as respondents. The instrument by collecting data from respondents is a questionnaire using a Likert scale with 10 statements compiled. From the results of the study, students still carried out basketball extracurricular activities even though it was still a COVID-19 pandemic in accordance with the coach's directions including physical activities and movement techniques. Based on the results of the junior high school basketball extracurricular survey research in Bangkalan Regency during the COVID-19 pandemic, it can be interpreted that students are still doing physical activities and playing basketball and coaches are still providing training directions to students who take basketball extracurricular activities even though it is still a pandemic. In the implementation of extracurricular during the COVID19 pandemic Key words: COVID-19, Extracurricular, Basketball